(untitled) (Pakistan Journal of Engineering, Technology and Science, 2024)
The Intelligent Transport System (ITS) comprehends an extensive range of applications, talking zones for instance road safety, comfort, security, and traffic flow. It is vital to defense reserved facts, and the revocation of harmful vehicles should only occur once malicious committed is noticed. Mechanisms of ITS include Vehicles (Vs), Certification Authority (CA) and Road Side Units (RSUs). It is seemly not to expose the real distinctiveness of an ITS station that is a vehicle, during the communication. Through the swift progresses in vehicle technologies, extraordinary throughput satellite communiqué, cyber physical systems, Internet of Things (IoT) and the Internet of Vehicles (IoV) have developed as a substantial research effort for expressive applications in current ages. IoV empowers linked and autonomous vehicles to involve with ITS environments, covering infrastructure, computing nodes, sensors and other entities. Vehicular ad hoc networks (VANETs) donate to develop driving efficacy and protection by dropping traffic congestions and avoiding accidents. However, the ad hoc nature of VANETs leads weaknesses, leading to numerous types of likely attacks. These attacks result in the deprivation of VANETs, tolerating malicious vehicles to misinform lawful vehicles for personal gain. To achieve the objectives of VANETs, it is vital to implement forceful security procedures. Though various techniques have been suggested but face different challenges such as communication delays, computational overheads and security. This learning suggests an efficient hash based method considered to ease communication delays, computational overheads and security attacks. The results specify that the proposed prototypical shows to be operative in addressing these challenges.